Pengembangan Video Tutorial Make up Flawless Pada Modifikasi Tata Rias Pengantin Sunda Putri - Febrianti, Shafira; Irtawidjajanti, Sri (Universitas Negeri Jakarta, 2023)
The development of this video tutorial was carried out to provide benefits and explanations to students and the public regarding the development of facial make-up for traditional Sundanese female brides, becoming modified Sundanese female brides which are currently trending, namely Flawless Make-up, flawless make-up which has characteristics such as natural make-up with use colors that are still soft natural, that is, you still look like you are wearing make up but with neater and glowing results, for example using soft pink and soft peach colors. The aim of this research is to produce a Video Tutorial for Flawless Make Up on Modifying Sundanese Women's Bridal Makeup that is suitable for production. This research method uses the ADDIE R&D research model which is used to produce certain products and test the effectiveness of the video. The process in this video consists of pre-production planning, production, post-production, research process, data processing and research results. The results of making this video tutorial meet the validation criteria obtained by material and professional experts, namely 81% and by media experts, 100%. It can be concluded that this video is very suitable to be used as a learning medium for students in the Indonesian Bridal course in the Middle Part of the Cosmetology Study Program.